Malignant melanoma: surgical treatment - D'Auria, Agustín (Cirugía del Uruguay, 1974)
Treatment of primary melanoma lesions is surgical. Resection must include an 8 x 4 cmt. ellipse, with its long axis oriented toward the regional lymph nodes. The procedure must be performed in most cases under regional or general anesthesia. The cutaneous opening must be covered with a split-thickness skin graft. Out of 50 cases of resections st